Factors influencing the intention to participate in motor takaful among JAKIM staff - Mohd naim, Mustafa (2020)
After 30 years of the commencement of takaful industry in Malaysia, motor takaful, as the shariah compliant choice, is still lagging far behind conventional insurance in term of market penetration. Domination of conventional insurance in this industry is still undeniable. The intention of Muslims to participate in motor takaful may give answer to takaful low penetration and domination of this industry in Malaysia. For that, this study aimed to look at the factors that influenced the intention to participate in motor takaful, particularly among Jabatan Kemajuan Islam Malaysia (JAKIM) staff in Putrajaya. Applying the Theory of Reasoned Action (TRA), questionnaires were distributed and analysed to measure the intention of JAKIM staff toward their participation in motor takaful. Multiple Linear Regression (MLR) was carried out to analyse the relationship between the independent variables and the dependent variable. The results showed that subjective norm does not significantly affect the dependent variable. Risk awareness and attitude significantly influence the intention to participate in motor takaful. This study provides a better understanding of the factors influencing the intention of vehicle users in choosing takaful. This study is important as one of the small contributions, especially to takaful operators in empowering takaful industry, specifically, and for Islamic financial system, generally, in Malaysia.